A model for selecting project team members using multicriteria group decision making - Alencar,Luciana Hazin (2010)
Selecting a project team is a complex multi-criteria decision-making problem. For this reason, one appropriate way to tackle such problems involves the use of multi-criteria decision aid methods. However, most of the decisions taken regarding the selection of project teams are made by a group of people. It is this which changes the focus of the problem by moving from one decision-maker (DM) to a group of DMs. Analysis needs to be extended in order to consider the preference structure of each individual group member. In this paper, we present a group decision model for project team selection based on a multi-criteria evaluation of the preferences of a client's representatives. It could be applied to any decision problem since it involves a group of decision makers whose preferences diverge little. An application of the model in order to select consultants for a construction project is presented.